Design of polymeric auxetic matrices for improved mechanical coupling in lead-free piezocomposites. (1st April 2020) - Krishnaswamy, Jagdish A; Buroni, Federico C; Melnik, Roderick; Rodriguez-Tembleque, Luis; Saez, Andres
Abstract: While lead-free piezocomposites offer an environmentally friendly solution to mechanical sensing and energy harvesting, they lag state-of-the-art lead-based materials in terms of performance. It is therefore important to develop new material designs to bridge this performance gap. Considering composites where rigid piezoelectric inclusions are embedded in soft matrices, a major cause of poor performance is weak coupling of applied strains to the inclusions. We show here that by designing matrices with negative Poisson's ratios (auxetic matrices) it is possible to considerably improve this coupling. We first demonstrate this concept using a matrix which is inherently auxetic where we show an improvement of 40%–50% in the piezoelectric response. Based on the observations made, we develop a scalable design for auxetic matrices using conventional non-auxetic polymeric materials. This is done by embedding rigid auxetic structures in softer matrices. We show that with such designed auxetic matrices, which are amenable to fabrication through 3D printing, it is possible to achieve considerably larger piezoelectric response with a significant retention of the matrix softness. Particularly, we show that auxetic designs can show piezoelectric enhancements exceeding 300% compared to non-auxetic reference designs having similar a non-auxetic rigid backbone of similar volume as the auxetic backbone. Therefore, the use of matrices with negative Poisson's ratios is a promising design avenue to decouple mechanical coupling of strain to inclusions and matrix hardness. This strategy can pave way to design of softer piezocomposites with superior responses employing only structured polymeric materials without the use of expensive nanomaterials.